2011
DOI: 10.2478/s11535-011-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and biochemical response in rats on intratracheal instillation of manganese

Abstract: Chronic exposure to excess manganese via inhalation of metal fumes causes central nervous system damage. For modelling Mn aerosol inhalation, male Wistar rats were intratracheally instilled with MnCl2 solution (0.5 mg/kg b.w. MnCl2; n=12) 5 days a week for 5 weeks. At the end of the treatment, somatosensory cortical evoked potentials, elicited by double-pulse stimulation, were recorded from the animals in urethane anaesthesia. Body weight gain, organ weights, and Mn level in brain, lung and blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Based on the health importance of human exposure to airborne Mn-containing NPs, the need for neurotoxicological assessment of MnO 2 NPs (stressed by Li et al [9]), and on our previous experience with modeling such exposure in rats [29][30][31], the aim of the present study was to investigate the effect of particle size, within the nano range, on the general and nervous system toxicity of MnO 2 NPs in subacutely treated rats.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the health importance of human exposure to airborne Mn-containing NPs, the need for neurotoxicological assessment of MnO 2 NPs (stressed by Li et al [9]), and on our previous experience with modeling such exposure in rats [29][30][31], the aim of the present study was to investigate the effect of particle size, within the nano range, on the general and nervous system toxicity of MnO 2 NPs in subacutely treated rats.…”
Section: Introductionmentioning
confidence: 99%
“…Previous own studies on the neurotoxicity of Mn revealed, as the main electrophysiological alteration in rats, a latency lengthening of cortical sensory EPs, observed after several weeks of Mn exposure by the oral route (dissolved MnCl2: Vezér et al 2005) or by intratracheal application of dissolved (Máté et al 2011) or nanoparticulate Mn (MnO2 nanoparticles (NPs): Oszlánczi et al 2010). Parallel shift of the spontaneous cortical activity to higher frequencies was also observed.…”
Section: Introductionmentioning
confidence: 86%